Achieving the Sustainable Development Goals (SDGs) and the Intricacies and Dynamics of Development Administration - Kayode Asaju (Journal of Contemporary Sociological Issues, 2022)
Development administration is primarily concerned with the various strategies to achieve accelerated national development, especially in developing countries. One major instrument for achieving national development objectives is the development plan. The development plan stipulates development goals and targets, various policies, programs and projects, and finances to achieve the objectives of national development. However, despite all these efforts in Nigeria, it seems the level of underdevelopment is still high considering the various obvious statistics and realities on the ground. The paper examines the efforts of the government at national planning over the years and the achievement made so far on SDGs. It identified the intricacies and dynamism involved over time in the achievement of SDGs and as well proffers solutions for better management. Secondary data was derived from books, journals, online publications, and government official reports in gathering information for the paper. Content ana lysis was adopted in analyzing the data collected. The study concludes that attempts at achieving the various targets of the SDGs were not successful due to certain inherent peculiarities in Nigeria. The high level of poverty, unemployment, inequality and insecurity, low infrastructural development, and poor social services like education, health services, housing, electricity, etc. are peculiar indicators of these failures. The paper suggests among others: the building of institutional capacity and fit for governance, the need to confront the structural impediments confronting attempts at achieving public policy through a constitutional review, emphasis on infrastructural development adequate for achieving national development and enhancing technological development, and capacity building through a viable and efficient educational sector. Keywords: Development, Development Administration, Sustainable Development, National Development